Exploring Student Errors in Solving Derivative Problems: A Systematic Literature Review - Syaputra, Muhammad Rizky; Juandi, Dadang; Kusnandi, Kusnandi; Elsa, Hanne Ayuningtias (FKIP Universitas Lampung, 2024)
Derivative material is essential in developing students’ critical thinking skills and its application in various scientific fields, specifically in mathematics. However, numerous studies revealed that many students still considered this material difficult, which often causes students to make mistakes in solving derivative problems. This study aims to analyze students' errors in solving derivative problems. This research method used systematic literature review with data synthesis process, qualitative data analysis through thematic analysis, and PRISMA method for data selection which obtained 10 articles from 232 articles on the Google Scholar, Semantic Scholar, and Scopus pages. The analysis results showed uneven fluctuations in the number of studies, peaking in 2022. The distribution of research covers nine provinces in Indonesia, with a dominance in the NTB province, although the distribution is still uneven. Newman’s theory became the primary approach to analyzing student errors. Most of the research was published in SINTA 4 and SINTA 5 journals, while contributions in highly reputable journals are still minimal. The most dominant student error occurred at the encoding/looking back stage, which was caused by a lack of understanding of the derivative concept, inaccuracy, rushing, and lack of habit to re-examine the work. Other errors include conceptual, procedural, and technical errors related to derivative facts, concepts, operations, and principles. As a solution, interactive teaching materials based on the Newman procedure was recommended to improve students’ understanding of derivative concepts. Keywords: derivative, mathematics, student errors, systematic literature review. DOI: http://dx.doi.org/10.23960/jpmipa/v25i4.pp1693-1704